2021
DOI: 10.3390/ijerph18031286
|View full text |Cite
|
Sign up to set email alerts
|

Increased Alopecia Areata Risk in Children with Attention-Deficit/Hyperactivity Disorder and the Impact of Methylphenidate Use: A Nationwide Population-Based Cohort Study

Abstract: Alopecia areata (AA) is an autoimmune disease that causes sudden hair loss. Although few studies have reported the association between AA and attention-deficit/hyperactivity disorder (ADHD), the impact of methylphenidate (MPH) on AA has not been examined. This study examined whether AA risk is higher in children with ADHD than in those without ADHD as well as the impact of MPH use on AA risk in children with ADHD. From the Taiwan Maternal and Child Health Database, we enrolled all 1,750,456 newborns from 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Dermatology 2024;240:13-25 DOI: 10.1159/000533366 [65], albinism [66], ichthyosis [67,68], and alopecia areata [69] were reportedly associated with ADHD, although most evidence was based on cross-sectional studies.…”
Section: Associations Of Ad With Adhd and Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatology 2024;240:13-25 DOI: 10.1159/000533366 [65], albinism [66], ichthyosis [67,68], and alopecia areata [69] were reportedly associated with ADHD, although most evidence was based on cross-sectional studies.…”
Section: Associations Of Ad With Adhd and Asdmentioning
confidence: 99%
“…The prevalence was significantly higher than the general population Albinism A study from the USA indicated an ADHD prevalence rate of 22.7% in children and 6.8% in adults, with the combined hyperactivity and impulsivity subtype of ADHD being the most common diagnosis [66] Ichthyosis The prevalence of ADHD was increased in patients with ichthyosis vulgaris (6.1%) and X-linked ichthyosis (13.1%) [67]. X-linked ichthyosis may be a risk factor for ADHD with predominantly inattentive symptoms [68] Alopecia areata In a cohort study using Taiwan's nationwide registries, the risk of alopecia areata was higher in children with ADHD than in those without (HR: 1.30; 95% CI: 1.04-1.64) [69] AD, atopic dermatitis; ADHD, attention deficit/hyperactivity disorder; CI, confidence interval; HR, hazard ratio; OR, odds ratio.…”
Section: Skin Diseases Findingsmentioning
confidence: 99%
“…Another hypothesis suggests that this dermatologic disorder may share some etiologic factors with psychopathologic disorders of childhood, and it has been suggested that the alopecia areata and ADHD may share common underlying mechanisms. A nationwide study conducted by Ho et al revealed that alopecia areata risk was higher among ADHD patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients not receiving methylphenidate had an insigni cant reduced risk of developing alopecia areata compared to those who were receiving the treatment (13). Patients with dermatologic disorders are not the only ones who deal with behavioral and psychopathologic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты показали, риск развития данной патологии у этих детей был выше по сравнению с группой детей без данного синдрома. Авторы доказали, что функциональные нарушения мозгового кровотока являются одной из причин развития гнездной алопеции у детей [29], так как обеднение микроциркуляторного русла дермы приводит к нарушениям трофики дермальной папиллы.…”
Section: ____________________________________________________________...unclassified